2020
DOI: 10.2147/ndt.s280047
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Orthorexic Tendencies with Obsessive-Compulsive Symptoms, Eating Attitudes and Exercise</p>

Abstract: Purpose The term orthorexia nervosa is used to describe the pathological fixation associated with consuming healthy food. It is assumed that orthorexia nervosa shares some phenomenological features with anorexia nervosa, obsessive-compulsive disorder (OCD), and other mental disorders. Individuals with orthorexic tendencies may have high physical activity as well as a healthy diet. This study aimed to investigate the relationship of orthorexia nervosa with obsessive-compulsive symptoms, eating atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
1
17
1
2
Order By: Relevance
“…Numerous studies showed a positive association between ON and physical activity or exercise addiction [49,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. Segura-García et al [81] indicated athletes presented higher ON scores than the control group.…”
Section: The Relationships Between Physical Activity Orthorexia and Fear Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies showed a positive association between ON and physical activity or exercise addiction [49,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. Segura-García et al [81] indicated athletes presented higher ON scores than the control group.…”
Section: The Relationships Between Physical Activity Orthorexia and Fear Of Covid-19mentioning
confidence: 99%
“…Bert et al [71] found that ON (using EHQ) can be predicted by endurance sport practice (sports with predominantly aerobic activity > 150 min/week) in Italian athletes (b = 2.407, 95% CI = 0.27;4.54). Moreover, Yılmaz et al [84] found higher orthorexic tendencies (ORTO-15) in participants who regularly performed physical exercises than those diagnosed with obsessive-compulsive disorder (OCD) and healthy individuals who did not perform physical exercises.…”
Section: Associations Between Variablesmentioning
confidence: 99%
“…This nding reveals that the two conditions may have similar cognitive and behavioral characteristics, as some authors suggest [48]. For example, individuals with ON spend most of their time in ritualistic behaviors and excessive efforts to select and prepare healthy food, similar to patients with obsessive and compulsive disorder (OCD) [49]. Moreover, ON is typically characterized by obsessions (e.g., overthinking about food preparation, in ated concern over contamination and impurity) and impaired social functions like OCD [50].…”
Section: Discussionmentioning
confidence: 58%
“…They did not find a significant difference between the two groups; however, they did determine that a higher volume of exercise significantly affects the risk for ON behavior. Moreover, recently, a study was conducted in Turkey on patients with obsessive compulsive disorder (OCD), physically active healthy controls and non-active controls [44]. The findings showed that physically active individuals had the highest ON tendencies between the three groups.…”
Section: Discussionmentioning
confidence: 99%